MSME Governance and Digitalization Model in Lauwonu Village - Sri Indriyani Rahman; Sahmin Noholo; Yustina Hiola (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze business governance practices and the use of digital technology in MSMEs in Lauwonu Village, Tilango District, Gorontalo Regency, and to develop a digital-based governance model relevant to MSMEs. The study used a qualitative approach with the Participatory Action Learning System (PALS) method developed by Mayouk in 2000. Data collection techniques were carried out through observation, interviews, documentation, and mentoring of six MSMEs in Lauwonu Village. Data analysis was carried out through data reduction, data presentation, and drawing conclusions/verification using triangulation of sources and techniques to maintain data validity. The results of the study indicate that MSME governance in Lauwonu Village is still not running optimally. Most MSMEs have not recorded and reported their finances routinely and systematically. Financial management is still carried out simply and some business actors still mix personal and business finances. The use of digital technology is also still limited, although some MSMEs have used Microsoft Excel and the Buku Kas application. Through mentoring activities, MSMEs began to understand the importance of financial recording and the use of digital technology in business management.